Gimnasia aeróbica y su incidencia en los hábitos sedentarios en las amas de casa de la ciudadela Los Laureles del Cantón Babahoyo, Provincia los Ríos en el año 2016 - Jara Arbelae, Gloria Veronica (2016)
The work entitled AEROBIC GYMNASTICS AND ITS IMPACT ON HABITS SEDENTARY HOUSEWIVES OF THE CITADEL “THE LAURELES” BABAHOYO CANTON PROVINCE RIVERS IN THE YEAR 2016, includes the results of studies, diagnosis and correlational referred to the incidence of Aerobic gymnastics in the state of health practitioners, for development and taking into account demands of research were used, methods of scientific research and mathematical and statistical methods. The work was done with the participation of practitioners and teachers, selected from the universe of these. In the proposed research activity is expected to achieve results that from the point of theoretical and practical, will meet the demands of many teachers and practitioners of Canton